2010
DOI: 10.1590/s0066-782x2010000300003
|View full text |Cite
|
Sign up to set email alerts
|

Malformações cardíacas congênitas em necropsias pediátricas: características, associações e prevalência

Abstract: Background: In Brazil, since 2001, the congenital abnormalities have represented the second cause of death in children younger than one year, with cardiovascular defects being responsible for 39.4% of these deaths.Objectives: To establish the prevalence and the characteristics of the congenital cardiac malformations in pediatric necropsies performed in Hospital Regional da Asa Sul, Brasília, DF, Brazil, from January 1996 to December 2007.Methods: This is a descriptive, cross-sectional study that reviewed 1,591… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 13 publications
1
7
0
8
Order By: Relevance
“…development, among them are: intra and extraoral hypotonia, labial closure and control of tongue movements changed being movements of tongue and jaw fundamental for milking and coordination of sucking, swallowing and breathing and labial essential so that there is intraoral pressure essential to the effective suction 10,11 . In pediatric cardiac population, are considered risk factors for oropharyngeal dysphagia: less than three years old, greater than seven days of intubation, preoperative intubation and operations for obstructive lesions of the left side 6 , corroborating the present study, in which both infants showed the symptom and at least two risk factors mentioned above.…”
Section: Figure 4 -Results Of Clinical Evaluation Through Instrument supporting
confidence: 91%
See 2 more Smart Citations
“…development, among them are: intra and extraoral hypotonia, labial closure and control of tongue movements changed being movements of tongue and jaw fundamental for milking and coordination of sucking, swallowing and breathing and labial essential so that there is intraoral pressure essential to the effective suction 10,11 . In pediatric cardiac population, are considered risk factors for oropharyngeal dysphagia: less than three years old, greater than seven days of intubation, preoperative intubation and operations for obstructive lesions of the left side 6 , corroborating the present study, in which both infants showed the symptom and at least two risk factors mentioned above.…”
Section: Figure 4 -Results Of Clinical Evaluation Through Instrument supporting
confidence: 91%
“…face , infants with Down syndrome, in 43% of cases, has congenital heart disease that is often corrected by surgery 3 . Congenital heart disease refers to abnormalities that occur before birth in the structure or function of the heart, it is estimated that every 1,000 births four to 50 infants possess this amendment, which still represents a major cause of infant mortality in the United States and the second largest in Brazil [4][5][6] . The necessary surgeries usually weaken the general health and the quality of life of the patients 5,6 .…”
Section: Casuistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicate that chromosomal diseases, especially trisomies, have a high prevalence of heart disease in all age groups [27,28]. These statements may explain the low levels found in some KTK tasks, especially those involving jumps, in which individuals were tired quickly, since the need to jump as fast as possible.…”
Section: Discussionmentioning
confidence: 99%
“…é um tópico que merece atenção. As anomalias cardíacas congênitas têm apresentação variada e podem progredir sem sintomas associados, até os relacionados à sintomatologia e à alta mortalidade, traduzindo a variedade e os graus de comprometimento estrutural cardiovascular observados morfologicamente (5,6) .…”
Section: Introductionunclassified